Amniotic and cervical fluids progranulin levels in pregnancies complicated by spontaneous preterm delivery with respect to intra-amniotic complications-a retrospective cohort study - Soucek, Ondrej; Kacerovsky, Marian; Musilova, Ivana; Kukla, Rudolf; Bolehovska, Radka; Bostik, Pavel; Jacobsson, Bo; Andrys, Ctirad (Scientific reports, 2025)
The main aim of the study was to determine progranulin levels in amniotic and cervical fluid samples from pregnancies complicated by preterm prelabor rupture of membranes (PPROM) or preterm labor with intact membranes (PTL), with concomitant microbial invasion of the amniotic cavity and/or intra-amniotic inflammation. A total of 104 and 108 women with PPROM and PTL, respectively, were included. Paired amniotic and cervical fluid samples were obtained using transabdominal amniocentesis and Dacron polyester swabs, respectively. Progranulin levels were assessed with an enzyme-linked immunosorbent assay. Women with PPROM and PTL were divided into subgroups based on microbial invasion of the amniotic cavity and/or intra-amniotic inflammation. Differences in progranulin levels among the PPROM and PTL subgroups were found in amniotic fluid: (a) PPROM: intra-amniotic infection: 51.8 pg/mL, sterile intra-amniotic inflammation: 52.8 pg/mL, colonization: 36.4 pg/mL, and negative amniotic fluid: 35.0 pg/mL; p < 0.0001; (b) PTL: intra-amniotic infection: 75.3 pg/mL, sterile intra-amniotic inflammation: 54.0 pg/mL, and negative amniotic fluid: 39.1 pg/mL; p < 0.0001. The corresponding differences were not found in cervical fluid: (a) PPROM: p = 0.14; (b) PTL: p = 0.53. In conclusion, amniotic fluid progranulin levels increased in PPROM and PTL cases with concomitant intra-amniotic inflammation, regardless of whether microbial invasion of the amniotic cavity was present or absent.
Keywords: Microbial invasion of the amniotic cavity; předčasný odtok plodové vody; plodová voda; retrospektivní studie; Chorioamnionitis; předčasný porod; Pregnancy; těhotenství; Adult; Obstetric Labor, Premature; Progranulins; dospělí; Premature Birth; amniocentéza; Preterm delivery; Intra-amniotic inflammation; Fetal Membranes, Premature Rupture; předčasná porodní činnost; Amniotic Fluid; Invasive sampling; lidé; chorioamnionitida; ženské pohlaví; Humans; cervix uteri; Amniocentesis; Retrospective Studies; Amniotic fluid; Non-invasive sampling; progranuliny; Female; Cervix Uteri